A closed-tube, single-step, real time, reverse transcription-loop-mediated isothermal amplification assay for infectious bronchitis virus detection in chickens - El-Tholoth, Mohamed (J Virol Methods, 2020)
Infectious bronchitis (IB) is a viral infection of the chicken respiratory tract that causes substantial economic burden on the industry. Simple, specific and rapid diagnosis of this disease is critical for the initiation of appropriate control measures. Conventional molecular diagnostic methods require a relatively sophisticated equipment and skilled staff. Here we describe a rapid, simple, semi-quantative, closed-tube, single-step, real-time- reverse transcription-loop-mediated isothermal amplification (RT-LAMP) assay for IB and compare our assay with quantative, reverse transcription- polymerase chain reaction (RT-qPCR). The limit of detection (LOD) of our RT-LAMP assay is 1 EID(50)/ ml. Clinical evaluation of samples from diseased chickens with our RT-LAMP showed a very good concordance with RT-qPCR. Our assay enables simple, specific, rapid molecular detection and semi-quantification of the infectious bronchitis virus (IBV) in veterinary diagnostic laboratories. Furthermore, our RT-LAMP detection is carried out in a sealed tube, eliminating the risk of false-positive results in subsequent tests because of any contamination of the work area as in the case of lateral ﬂow strip or gel electrophoresis-based amplicon detection.